CRISPR-CAS9 MEDIATED GENETIC ENHANCEMENT OF DROUGHT TOLERANCE IN MAIZE: A MOLECULAR AND FIELD VALIDATION STUDY - Muhammad Hazmi; Zain Nizam; Nina Anis (Research of Scientia Naturalis, 2025)
Drought is a primary constraint on maize (Zea mays L.) productivity worldwide, threatening global food security. The development of climate-resilient crops is therefore a critical priority. This study aimed to enhance drought tolerance in maize by utilizing the CRISPR-Cas9 system to edit a key negative regulator gene involved in the drought stress response pathway. The research employed an Agrobacterium-mediated transformation method to introduce the CRISPR-Cas9 construct into maize embryos. Putative edited plants were rigorously screened using molecular techniques, including PCR and Sanger sequencing, to confirm successful gene modification. Validated T1 generation lines were then subjected to controlled drought stress conditions in greenhouse trials and subsequently evaluated in multi-location field trials. The edited maize lines exhibited significantly improved physiological and agronomic performance under water-deficit conditions, including enhanced photosynthetic efficiency, reduced leaf water loss, and a 15-20% increase in grain yield compared to non-edited wild-type controls. This study demonstrates the efficacy of CRISPR-Cas9 for developing drought-tolerant maize, offering a precise and rapid strategy for crop improvement to mitigate the impacts of climate change.